Liminal Performance and Gender Reconstruction: Exploring Subaltern Consciousness in Balidaan - Bhusal, Tilak; Bhattarai, Krishna Prasad (Curriculum Development Journal, 2025)
Balidaan is a highly acclaimed film that redefines gender boundaries within a historical context. This paper examines the portrayal of subaltern consciousness, manifested through revolutionary songs, inclusive representations of ordinary people, underground resistance movements, and their collective struggle against autocratic rule. The film critiques the cruelty and domination of the Panchayat regime, highlighting the suffering of ordinary Nepalese citizens and their resistance against systemic oppression. Central to this analysis is exploring the subaltern voice and agency, which emerges through the active participation of marginalized individuals and rebel groups in dismantling autocratic hierarchies. The paper also investigates the redefinition of gender boundaries within these revolutionary dynamics, underscoring how collective resistance challenges oppressive norms. These issues are analyzed through the theoretical frameworks of liminal performance pedagogy and subaltern consciousness, offering insights into the intersection of  marginality, resistance, and transformative action.